Eternal love - Riesenfeld, Hugo 1879-1939; Heer, Jakob Christoph 1859-1925 (Milestone, 1998)
Amazing for a silent-era film, Ernst Lubitsch's story of love, war, and tragedy on a Swiss mountaintop will have you in tears by its finale. John Barrymore is typically stoic as the hero, a hunter who, during the 1806 occupation by French soldiers, refuses to hand in his gun - the desperado of the village. He needs his gun to protect his lady friend, Ciglia (Camilla Horn), with whom he is deeply in love. Alas there's also a troublesome mountain girl named Pia (Mona Rico), who's making a testy situation even worse. Pia engineers trouble, and soon our two heroes are on the run for their lives ... and their love. Sounds sappy, but the photography is unforgettable and the finale is devastating.